2013
DOI: 10.3892/ol.2013.1338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four serum microRNAs from a genome-wide serum microRNA expression profile as potential non-invasive biomarkers for endometrioid endometrial cancer

Abstract: Serum microRNAs (miRNAs), with their remarkable stability and unique concentration profiles in patients with various diseases, are promising non-invasive biomarkers for tumor detection. The present study investigated the altered profiles of serum microRNAs in patients with endometrioid endometrial cancer (EEC) in order to predict the malignancy of the disease at a relatively early stage. TaqMan® low-density arrays (TDLAs) were used to perform an analysis in the initial screening phase using serum samples poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…Continuous elucidation of miRNA functions augments the potential of these regulatory nucleic acid elements to either be implemented as useful biomarkers in disease/malignancy diagnosis, prognosis and therapy monitoring, as well as novel therapeutic targets ('AntagomiRs') in clinical cancer management (1,21,93). The potential applicability of circulating miRNAs as non-invasive biomarkers for diagnosis (32) or as therapeutic targets (94,95) in EC is currently subject of various studies. In this context this in vitro model may serve as initial step to elucidate the influence of microenvironmental changes on expression profiles of circulating microRNAs in EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous elucidation of miRNA functions augments the potential of these regulatory nucleic acid elements to either be implemented as useful biomarkers in disease/malignancy diagnosis, prognosis and therapy monitoring, as well as novel therapeutic targets ('AntagomiRs') in clinical cancer management (1,21,93). The potential applicability of circulating miRNAs as non-invasive biomarkers for diagnosis (32) or as therapeutic targets (94,95) in EC is currently subject of various studies. In this context this in vitro model may serve as initial step to elucidate the influence of microenvironmental changes on expression profiles of circulating microRNAs in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, distinct miRNA signatures characterizing EC subtypes have been described (24,(27)(28)(29)(30). Since miRNAs have been shown to be stable molecules which are well preserved in serum and other body fluids (21,31,32) their use as promising non-invasive biomarkers in EC is under investigation (21). Jia et al reported in 2013 the identification of four serum-based miRNA types as potential non-invasive biomarkers for endometrioid endometrial cancer (32).…”
Section: Hypoxia-and Acidosis-driven Aberrations Of Secreted Micrornamentioning
confidence: 99%
“…For example, miR-186 expression is upregulated in non-small cell lung cancer and bladder cancer but downregulated in pancreatic cancer and endometrial carcinoma. [26][27][28][29] miR-186 was reported to be minimally expressed in glioma and exhibits a tumor suppressive effect, inhibiting glioma stem cell proliferation, migration, and invasion. 45 To study the effect of miR-186 on glioma vascular endothelial cells, we detected the expression level of miR-186 in glioma-conditioned vascular endothelial cells and found that miR-186 expression was downregulated in glioma-conditioned hCMECs.…”
Section: Discussionmentioning
confidence: 99%
“…It is upregulated in pancreatic and endometrial cancers, but downregulated in non-small cell lung cancer, glioma, and medulloblastoma. [26][27][28][29][30] However, the function of miR-186 in glioma vascular endothelial cells remains unclear.…”
Section: Pvt1 Affects Growth Of Glioma Microvascular Endothelial Cellmentioning
confidence: 99%
“…Previously, miR-186-5p expression has been reported as up-regulated in several different malignancies [99][100][101][102][103][104]130]. Furthermore, miR-186 has demonstrated an oncogenic function via its down-regulation of anti-tumor associated genes in cancer.…”
Section: Validation Of Mirnasmentioning
confidence: 99%